Warm-Up Programs as a Key Strategy for Injury Prevention in Youth Sports: Warm-Up Programs for Injury Prevention in Sports - Khan, Shahzaman (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2026)
Sports injuries are common injuries that happen when you’re playing a sport or doing something athletic. Participation in athletic activities naturally increases the likelihood of injury. Involvement in sports is a primary cause of injuries among children and teenagers. Preventing injuries is crucial for athletes to avoid long-term problems and continue enjoying their favorite sports. Common sports injuries stem from preventable circumstances such as poor training practices, improper gear, or a lack of warming up. This causes sprains, strains or tears mostly in joints and tendons. To prevent sports-related injuries, warm-up intervention programs can help reduce and minimize injuries. A warmed-up muscle is less likely to be strained than a cold one. Warm-ups prepare the body for exercise by increasing heart rate and improving blood flow to skeletal muscles [1, 2]. Warm-up activities consist of a sequence of exercises carried out prior to engaging in more intense physical activity. There are two types of warm-up techniques: passive and active. While passive warm-up is defined by a rise in muscle or core body temperature by external techniques, such as hot baths, saunas, or heating pads, active warm-up includes running, stretching, calisthenics, and some resistance workouts [1, 2]. According to a 1998 World Health Organization study on school-age children’s health habits, sports and playground activities accounted for 21.8% of injuries among children aged 11, 13, and 15 [3]. According to a separate survey, falls and sports-related injuries were the most common injury categories among male pupils between the ages of 10 and 14 [4]. In order to reduce the societal and personal costs associated with treatment and rehabilitation, initiatives aimed at preventing sports injuries in schools for kids and teenagers are essential. A recent systematic review and meta-analysis by Ding et al. summarizes the results of 15 high-quality studies that included more than 21,500 children and adolescents. The combined statistics indicate a significant reduction in the number of sports injuries- about 36 percent in total- proving that warming-up exercise is a quantifiable preventive measure. These interventions focused on neuromuscular control, balance, and strength were most effective, especially with middle school-aged participants and in sport-specific, non-school environments. Compliance was found to be a major moderator, and it is important to have a structured and consistent implementation to realize significant injury reductions [5]. The effectiveness of warm-up interventions holds significant clinical and practical relevance for physical therapists, physical education instructors, coaches, trainers, school officials, and community sports organizations involved in youth sports. The warm-up activities lowered the incidence of sports injuries (like acute or overuse injuries), consequently minimizing the related personal, social, and economic expenses, such as injury management, treatment, and rehabilitation. In conclusion, warm-up programs are important for keeping children and adolescents safe during sports. Regular and simple warm-up routines can help reduce injuries and support healthy physical activity. Coaches, teachers, and parents should make warm-ups a standard part of sports, as they are an easy and effective way to protect young athletes and improve performance.